1997
DOI: 10.1046/j.1365-2249.1997.4731373.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of soluble CD30 in patients with atopic dermatitis (AD)

Abstract: SUMMARYThe immunopathology of AD is still unclear, but evidence for an immune response polarized towards Th2 activity has been provided. The CD30 molecule belongs to the tumour necrosis factor (TNF) receptor family and is expressed on activated T cells with a sustained expression in Th2 cells. This molecule also exists in a soluble form (sCD30). Elevated serum levels of sCD30 have been found in patients with Hodgkin's disease, chronic hepatitis B infection and HIV infection. Studies were undertaken to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 24 publications
7
57
1
Order By: Relevance
“…If so, blockade of CD30-CD30 ligand signals might reflect the prolongation of eosinophil survival. Clinical observations that the level of sCD30 correlates positively with eosinophilia in Hodgkin's disease (51) and the serum eosinophil cationic protein level in patients with atopic dermatitis (41,42) are quite plausible if sCD30 can inhibit CD30-CD30 ligand signals in vivo (52). Needless to say, secretion of Th2-type cytokines might also participate the eosinophilia seen in these patients (77,78).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If so, blockade of CD30-CD30 ligand signals might reflect the prolongation of eosinophil survival. Clinical observations that the level of sCD30 correlates positively with eosinophilia in Hodgkin's disease (51) and the serum eosinophil cationic protein level in patients with atopic dermatitis (41,42) are quite plausible if sCD30 can inhibit CD30-CD30 ligand signals in vivo (52). Needless to say, secretion of Th2-type cytokines might also participate the eosinophilia seen in these patients (77,78).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble levels of CD30 are elevated and are associated with the prognosis in Hodgkin's disease and AIDS (38). Elevated levels were also reported in patients with adult T cell leukemia and some of those with non-Hodgkin's lymphoma, rheumatoid arthritis (39), chronic renal failure with primary growth retardation (40), atopic dermatitis (41)(42)(43), bullous pemphigoid (44), polymyositis/dermatomyositis (45), and helminth infection (46). Interestingly, some of these diseases are associated with eosinophilia (47)(48)(49)(50), and an especially positive correlation between the levels of soluble CD30 (sCD30) and eosinophilia was found in Hodgkin's disease (51).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CD30 was shown to be consistently expressed on a subset of lymphocytes known as Th2 cells (16), and accordingly, CD30 expression has been associated primarily with inflammatory disorders, such as atopic dermatitis (AD), that have a Th2 profile (17)(18)(19). However, it is now clear that Th1 and Th0 lymphocytes also express CD30 (20,21), and the distinction between Th1 and Th2 disorders based on CD30 expression is not absolute.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of TNF-alpha plasma levels and production by mononuclear cells in AD patients gave controversial results (19)(20)(21)(22). It should also be mentioned that CD30, which is a marker ofTh2 cell activation and whose soluble form is significantly elevated in AD, belongs to the TNF-receptor family (23). Recently, it has been found that TNF-alpha is the main inducer of inducible protein-It), belonging to the CXC chemokine subfamily, by skin fibroblasts from patients with atopic dermatitis (24).…”
Section: Resultsmentioning
confidence: 99%